Highly sensitive bend sensor based on bragg grating in eccentric core polymer fiber - Kalli, Kyriacos; Chen, Xianfeng; Webb, David J.; Zhang, Chi; Peng, Gangding (My University, 2010)
We report on an optical bend sensor based on a Bragg grating inscribed in an eccentric core polymer optical fiber. The device exhibits the strong fiber orientation dependence, the wide bend curvature range of ±22.7 m -1 and high bend sensitivity of 63 pm/m -1.
Keywords: Bragg gratings; Polymer optical fiber (POF); Bend sensor